2011
DOI: 10.1007/s00424-011-0975-9
|View full text |Cite
|
Sign up to set email alerts
|

Anoctamins

Abstract: Endogenous Ca(2+)-activated Cl(-) channels (CaCC) demonstrate biophysical and pharmacological properties that are well represented in cells overexpressing anoctamin 1 (Ano 1, TMEM16A), a protein that has been identified recently as CaCC. Proteins of the anoctamin family (anoctamin 1-10, TMEM16A-K) are widely expressed. The number of reports demonstrating their physiological and clinical relevance is quickly rising. Anoctamins gain additional interest through their potential role in cell volume regulation and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 121 publications
(186 reference statements)
4
98
0
1
Order By: Relevance
“…To that end we coexpressed different anoctamins together with P2Y 2 receptors in HEK293 cells, which were stimulated by 10 mM ATP, in the presence of a cytosol-like pipette filling solution and extracellular Ringer solution (see the Materials and Methods). We observed that overexpressed Ano1 and Ano6 produce significant whole-cell Cl 2 currents, even in the absence of ATP stimulation (Kunzelmann et al, 2011b). In cells expressing Ano1,4,7,8,9 and 10, whole-cell currents of variable magnitudes were activated by ATP (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…To that end we coexpressed different anoctamins together with P2Y 2 receptors in HEK293 cells, which were stimulated by 10 mM ATP, in the presence of a cytosol-like pipette filling solution and extracellular Ringer solution (see the Materials and Methods). We observed that overexpressed Ano1 and Ano6 produce significant whole-cell Cl 2 currents, even in the absence of ATP stimulation (Kunzelmann et al, 2011b). In cells expressing Ano1,4,7,8,9 and 10, whole-cell currents of variable magnitudes were activated by ATP (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…The relationship between ion channel currents, cell volume regulation, migration and metastasis is well established [30][31][32][33]. Previous findings indicate that Ano1 is activated during hypotonic cell swelling and contributes to regulatory volume decrease (RVD), which certainly requires a rise in intracellular Ca 2þ [5,27,34]. A rise in intracellular Ca 2þ may activate Ano1 together with K þ channels to release intracellular K þ and Cl 2 ions.…”
Section: Role Of Ano1 For Metastasismentioning
confidence: 99%
“…An additional suggestion for close association between Ca 2+ release sites and ANO1–CaCCs came from oocyte recordings: in oocytes overexpressing ANO1 and P2Y 2 receptors, whole‐cell currents activated by the Ca 2+ ionophore ionomycin displayed an outward rectification, while ATP‐activated currents had linear current–voltage relationships, suggesting higher local Ca 2+ concentrations near ANO1 channels in the latter case (Kunzelmann et al . 2011, 2012). …”
Section: Coupling Between Ano1 and Endoplasmic Reticulum; Is This A Gmentioning
confidence: 99%